Supplementary cementing materials - Siddique, Rafat; Khan, Mohammad bal 1962-.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
This book is an attempt to consolidate the published research related to the use of Supplementary Cementing Materials in cement and concrete. It comprises of five chapters. Each chapter is devoted to a particular supplementing cementing material. It is based on the literature/research findings published in journals/conference proceeding, etc. Topics covered in the book are; coal fly ash, silica fume (SF), granulated blast furnace slag (GGBS), metakaolin (MK), and rice husk ash (RHA). Each chapter contains introduction, properties of the waste material/by-product, its potential usage, and its effect on the properties of fresh and hardened concrete and other cement based materials.
FLY ASH -- SILICA FUME -- GROUND GRANULATED BLAST FURNACE SLAG -- METAKAOLIN -- RICE HUSK ASH.
Electronic reproduction.
Keywords: Cement; Electronic books